INFORMATION RESOURCES ANALYSIS IN ELECTRONIC CONTENT COMMERCE SYSTEMS - Lyubomyr CHYRUN; Victoria VYSOTSKA; Rostik LABA (Applied Computer Science, 2016)
The article is dedicated to the development of unified methods and soft-ware tools for processing information resources in the electronic content commerce systems. A new detailed classification of electronic commerce systems and electronic content commerce systems is proposed. A formal model and generalized typical architecture of electronic content commerce systems are declared. Architecture and models of electronic content commerce systems are built.